1973
DOI: 10.1063/1.1694258
|View full text |Cite
|
Sign up to set email alerts
|

Observation of ion heating near cyclotron harmonics using a radio frequency modulated electron beam

Abstract: Ion heating near the ion cyclotron frequency and its harmonics has been observed using a modulated electron beam injected into the low-density afterglow of a beam-generated plasma. Ion energies of 200 eV for He, 500 eV for D, and 700 eV for H have been measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Although ion heating was observed with density modulation at wj [29] it was reported that for n > 5 X 10 9 /c.c. the heating disappeared.…”
Section: Beam Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ion heating was observed with density modulation at wj [29] it was reported that for n > 5 X 10 9 /c.c. the heating disappeared.…”
Section: Beam Modulationmentioning
confidence: 99%
“…Low frequency beam modulation as a way of enhancing ion heating has been studied, using density modulation at noc [281, [29], and transverse modulation [30]. Although ion heating was observed with density modulation at wj [29] it was reported that for n > 5 X 10 9 /c.c.…”
Section: Beam Modulationmentioning
confidence: 99%